ENVIRONMENTAL IMPACT ASSESSMENT GUIDELINES FOR DEVELOPMENT IN COASTAL AREAS AND MARINE PARKS - Malaysia. Kementerian Sumber Asli dan Alam Sekitar. Jabatan Alam Sekitar, issuing body (Selangor : Ministry of Natural Resources and Environment Malaysia, 2017)
Includes bibliographical references.